Frequency response calculations of carbon nanotube based nanothermophones. (September 2020) - Hu, Hanping; Zhang, Kai; Wang, Dongdong
Abstract: Due to the extraordinary high thermal conductivity and low heat capacity, carbon nanotube (CNT) has shown a great potential as a thermo-acoustic (TA) material recently. It can be used to fabricate novel TA loudspeaker free of magnets and moving parts, a promising device that directly converts thermal energy into acoustic energy. In this paper, we have systemically analysed the frequency responses of the dot/wire/film TA emission from CNTs by using the equations we derived for acoustic field of TA emission from point source and arbitrary source. Formulas used for TA calculation from near-field to far-field can be the same. The dependence of sound pressure level (SPL)-frequcecy response of all kinds of CNT based nanothermophones on distance and angle are investigated in detail. It is found that TA sound pressure fluctuates in near-field, while increases linearly with logarithmic frequency in far-field. The amplitude of near-field fluctuation increases with increasing distance, but the frequency cycle of the fluctuation decreases and tends to be a constant depending on angle. These studies lay the foundation for further development of CNT based nanothermophones.